Doing and Undoing Wisdom: Reading Prov 10:1-22:16 as "Dynarchive" - Ehmer, Yannik (Hebrew bible and ancient Israel, 2024)
For a considerable period of time, scholars have interpreted Prov 10:1-22:16 as a random collection of sayings without any overarching compositional principles - and continue to do so. In turn, these scholars grant primacy to the analysis of the individual saying. This reluctance to examine and interpret proverbs contextually goes hand in hand with the rejection of proverbial self-reflection, i. e. paying attention to the traces of second-order thinking in proverbial wisdom. This article will suggest that proverbial wisdom is fundamentally critical, performative, and (implicitly) self-reflective. By looking closely at Prov 14:8-15 and Prov 16:16-17:3, through the hermerneutic lens of "dynarchive," i. e. a poetic archive in action, the analysis will unveil traces of second-order thinking in proverbial wisdom. By entangling multiple sayings that re-affirm, re-iterate, and sometimes even reverse each other, these passages become a performative exercise in epistemic humility.